Differences in sprinting and jumping performance between maturity status groups in youth: A systematic review and meta-analysis - Baker, J.; Read, P.; Graham-Smith, P.; Cardinale, M.; Jones, T. W. (Sports Medicine, 2025)
Background: Large interindividual differences can exist in the timing and tempo of growth and maturation of youth athletes. This can provide significant physical performance advantages to young athletes who mature in advance of their peers.